Holographic dynamics as a way to solve the basic cosmological problems - Bolotin, Yu.L.; Lemets, O.A.; Yerokhin, D.A.; Zazunov, L.G. (Вопросы атомной науки и техники, 2012)
We review recent results on the cosmological models based on the holographic principle which were proposed to explain the most of the problems occurring in the Standard Cosmological Model. It is shown that these models naturally solve the cosmological constant problem and coincidence problem. Well-documented cosmic acceleration at the present time was analyzed in the light of holographic dark energy. In particular, we showed that in the model of the universe consisting of dark matter interacting with a scalar field on the agegraphic background can explain the transient acceleration. We also study the impact of ideas of the physics of entangled states on these cosmological models. Entanglement entropy of the universe gives holographic dark energy with the equation of state consistent with the current observation data.